Literature Review: Analysis of Factors Influencing the Performance of Health Care Workers - Elfrida Jesika; Zairin Noor; Fauzie Rahman; Rosihan Adhani; Neka Erlyani (GLOBAL HEALTH SCIENCE GROUP, 2026)
Stunting is a chronic nutritional problem in toddlers influenced by various family factors. Maternal knowledge, parenting styles, and family income are thought to play a significant role in stunting. This study aims to synthesize scientific evidence regarding the relationship between these three factors and stunting in toddlers. This literature review analyzed case control articles published between 2022–2026 from PubMed, ScienceDirect, and Google Scholar based on inclusion criteria. The keywords used in the literature search for English-language journals included